Vegetation Dynamics Revealed by Remote Sensing and Its Feedback to Regional and Global Climate - Wang, Xuejia; Ou, Tinghai; Zhang, Wenxin; Ran, Youhua (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on some significant progress in vegetation dynamics and their response to climate change revealed by remote sensing data. The development of satellite remote sensing and its derived products offer fantastic opportunities to investigate vegetation changes and their feedback to regional and global climate systems. Special attention is given in the book to vegetation changes and their drivers, the effects of extreme climate events on vegetation, land surface albedo associated with vegetation changes, plant fingerprints, and vegetation dynamics in climate modeling.